2020
DOI: 10.1371/journal.pbio.3000838
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of humans and baboons suggests germline mutation rates do not track cell divisions

Abstract: In humans, most germline mutations are inherited from the father. This observation has been widely interpreted as reflecting the replication errors that accrue during spermatogenesis. If so, the male bias in mutation should be substantially lower in a closely related species with similar rates of spermatogonial stem cell divisions but a shorter mean age of reproduction. To test this hypothesis, we resequenced two 3-4 generation nuclear families (totaling 29 individuals) of olive baboons (Papio anubis), who rep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
109
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(122 citation statements)
references
References 91 publications
5
109
3
Order By: Relevance
“…The spectrum of mutations in the cat was remarkably similar to those found in most primates, with a preponderance of C>T and A>G transitions (Kong et al 2012;Venn et al 2014;Thomas et al 2018;Besenbacher et al 2019;Bergeron et al 2020;Wang et al 2020;Wu et al 2020;see Campbell et al 2020 for an exception in the mouse lemur). We showed that differences in the mutation spectrum between the cat and the human can in large part be explained by differences in age according to a model of reproductive longevity.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The spectrum of mutations in the cat was remarkably similar to those found in most primates, with a preponderance of C>T and A>G transitions (Kong et al 2012;Venn et al 2014;Thomas et al 2018;Besenbacher et al 2019;Bergeron et al 2020;Wang et al 2020;Wu et al 2020;see Campbell et al 2020 for an exception in the mouse lemur). We showed that differences in the mutation spectrum between the cat and the human can in large part be explained by differences in age according to a model of reproductive longevity.…”
Section: Discussionmentioning
confidence: 57%
“…Assuming the average parental age in our sample (3.8 years) is representative of the average age of reproduction in the cat, we estimate a per-year mutation rate of 2.2 × 10 -9 per bp. This is much higher than the human rate of 0.43 × 10 -9 per bp per year (Jónsson et al 2017), or the per-year rate from any reported primate (Besenbacher et al 2019;Campbell et al 2020;Wang et al 2020;Wu et al 2020). This higher rate is driven by the similar number of mutations at puberty, but a much shorter generation time in the cat.…”
Section: Mutation Rate In the Domestic Catmentioning
confidence: 69%
“…Several studies are lending support for the GL: in primates μ can be predicted via the reproductive longevity 15 and the mammalian male mutation bias is higher for species with long generation times 43 . There is evidence that this effect does not depend on the absolute number of cell divisions 44 . Also in invertebrates there is significant evidence for a correlation between rates of molecular evolution and generation times 11 .…”
mentioning
confidence: 98%
“…Nucleotide substitutions occur roughly 10 times more frequently than indels during germline cell replication. Genome-wide studies place the germline de novo mutation rate per nucleotide per generation at 1.2 × 10 −8 in humans, and 5.7 × 10 −9 in mice (Milholland et al, 2017 Processes shaping the germline genome germline mutational signaturesan increased proportion of paternally inherited versus maternally inherited mutationsis in part explicable as a consequence of the greater number of cell divisions involved in male reproduction (Haldane, 1947;Wilson Sayres & Makova, 2011;Jónsson et al, 2017;Wu et al, 2020; but see also Gao et al, 2018).…”
Section: Pre-meiotic Phasementioning
confidence: 99%
“…This is based on the observation that the yearly mutation rate estimated from human pedigree studies is almost half the rate inferred by looking at sequence divergence between human and chimpanzee (Pan troglodytes) genomes, suggesting a potential slowdown in mutation rate in humans (Scally & Durbin, 2012;Besenbacher et al, 2019). By contrast, in olive baboons (Papio anubis) the mutation rate appears to be lower than in humans (Wu et al, 2020).…”
Section: Pre-meiotic Phasementioning
confidence: 99%